STRATEGY FORMULATION FOR IMPLEMENTING HYBRID PROMOTIONS IN THE HOSPITALITY INDUSTRY: CASE STUDY OF HOTEL 1O1 STYLE YOGYAKARTA MALIOBORO - Agnes Ricarda Atik Damarjati; Sony Heru Priyanto; Sarbini Sarbini (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to formulate an experience- and relationship-based hybrid promotion strategy at Hotel 1O1 Style Yogyakarta Malioboro. Hybrid promotion is conceptualized not merely as the integration of online and offline channels, but as a comprehensive process of shaping guest experiences from the pre-visit stage through on-site service interactions that foster long-term relational bonds. This research employed a descriptive-exploratory qualitative approach, utilizing in-depth interviews, participant observation, and documentation involving management, staff, guests, and business partners. Data analysis was conducted thematically through open coding, axial coding, and selective coding, supported by triangulation and member checking to ensure data validity. The findings indicate that Integrated Marketing Communication plays a crucial role in forming initial guest expectations through consistent and coherent digital messaging. Furthermore, personal engagement during service delivery serves to validate these expectations through responsive, adaptive, and empathetic interactions. The emergence of marketing intimacy reflects the development of relational closeness, as evidenced by repeat visits, customer recommendations, and positive online reviews. This study proposes a hybrid promotion framework that is systematically integrated into service culture and strengthened through cross-departmental coordination to enhance customer experience and loyalty.